Structural characterization of uranium and lanthanide loaded borosilicate glass matrix - I. Tolnai; J. Osan; P. Jovari; F. Pinakidou; A. Sulyok; M. Fabian (Scientific Reports)
Abstract Borosilicate glass is a potential candidate for high-level radioactive waste conditioning, thus understanding the effects caused by the combined presence of uranium and actinides within these matrices is of great importance. The glass matrix was simultaneously loaded with UO3 and lanthanide oxides (CeO2, Nd2O3, and Eu2O3) as chemical surrogates for actinides. Neutron diffraction in combination with Reverse Monte Carlo simulation confirmed that the basic glass structure is comprised of tetrahedral SiO4, and BO3/BO4 units. X-ray absorption spectroscopy indicated the presence of Ce mainly as CeIII and the co-existence of UV and UVI. U acts as an intermediate oxide and reduces the number of four-coordinated B, lanthanide ions serve as modifiers, with their increasing concentration shifting the B-O coordination from 3 to 4. X-ray photoelectron spectroscopy revealed a depth-dependent variation in the UIV/UVI ratio. Leaching tests showed increased dissolution of Si, B, and Na, compared to the glass matrix.